An Pemberdayaan Ekonomi Pedesaan melalui Budidaya Jamur Tiram - Wibowo, Joko; Fahrurrozi, Fahrurrozi (Salwatuna : Jurnal Pengabdian Masyarakat, 2024)
The study investigated whether oyster mushroom cultivation could boost Bambang village’s economy. Its purpose was to assess cultivation’s impact on economic and social welfare, aiming to show how this agricultural initiative could enhance villagers'' livelihoods, provide stable income, and address social challenges by creating a supportive community. The research focused on improving both economic stability and social cohesion. The community service program included two main phases: training in oyster mushroom cultivation and forming a Women Farmers Group. The first phase provided two sessions with an expert, focusing on cultivation techniques. The second phase established a group for women in agriculture, fostering economic empowerment and sustainable skills with the support of a forest farmer group for resources and training. The community service program successfully trained 25 villagers in oyster mushroom cultivation, generating income and increasing economic resilience. Establishing the Women’s Farming Group further empowered women, promoting self-reliance in agriculture. These initiatives improved community knowledge and livelihoods. Plans include ongoing support for cultivation and marketing, alongside continued development of the Women's Farming Group to strengthen local economic growth. The community service programs in Bambang village effectively addressed the issues of low income, educational dropouts, and moral challenges by teaching oyster mushroom cultivation. This provided reliable income, enhanced social well-being, and empowered women through a farming group. The sustainable income potential revitalized community morale and plans aim to strengthen productivity, marketing, and cooperative development for lasting economic growth.